Telaah Kritis Hukum Islam terhadap Fenomena Salam Lintas Agama di Indonesia - M. Rahmad Azmi; Zulheldi Zulheldi (JURNAL ILMIAH PENELITIAN MAHASISWA, 2026)
This research is motivated by the ongoing debate surrounding the practice of interfaith greetings often referred to as greetings of diversity in Indonesia, particularly among Muslim public officials. The aim of this study is to explore in greater depth the underlying motives, interpretations, and experiences associated with interfaith greetings within the context of interreligious communication. This study employs a qualitative approach using the library research method, which involves collecting and analyzing data from a variety of written sources such as books, articles, and documents. The data were systematically reviewed, synthesized, and interpreted to derive meaningful conclusions. The findings of this research suggest that interfaith greetings may be permissible and functionally appropriate as opening remarks in gatherings attended by individuals of diverse religious backgrounds, provided they are intended solely as a form of social courtesy and not as a religious expression that compromises one's faith. In such cases, interfaith greetings can be understood as part of ḥablun min an-nās (maintaining good relations among people). However, if their use leads to negative implications for Islamic beliefs or promotes theological ambiguity, then such practice is deemed impermissible from an Islamic legal perspective.